Physicochemical and Sensory Properties of Bovine Milk Treated by Different UV-C Dose: The Effect on Vitamin D3, cholesterol, fatty acid, and formation of volatile compounds - Atik, Azize; Gumus, Tuncay; Karasu, Salih; Sagdic, Osman (UNIV ESTADUAL MARINGA, PRO-REITORIA PESQUISA POS-GRADUACAO, 2025)
This study investigated the effect of different UV-C doses on physicochemical (pH, color, viscosity) and sensory properties, FFA, vitamin D-3 , cholesterol, fatty acid composition, and oxidative volatile compounds formation. The physicochemical properties (pH, viscosity, and color) of milk were significantly affected by the application of UV-C and different UV-C doses (p < 0.05). The FFA of raw and pasteurized milk was determined as 0.053% and 0.10%, respectively. The FFA values significantly increased with the application of UV-C. The amount of cholesterol in UV-C-applied milk was in the range of 38.7449.70 ppm. The cholesterol level was significantly reduced by the application effect of UV-C treatment at all dosages (p < 0.05). The amount of vitamin D(3 )of raw and pasteurized milk was found as 90.91 mg kg(-1) and 65.87 mg kg(-1), respectively. The UV-C application at all dosages, with the exception of 98.4 J mL(-1), significantly increased the amount of D-3 (p < 0.05). UV-C application caused a significant change in the composition of fatty acid composition and this change varied according to applied UV-C dosage. The carbon disulfide and aldehyde formation rate increased and the sensory quality reduced as the UV-C dose increased.
Keywords: Bovine Milk; UV-C application; cholesterol level; vitamin D-3; ESCHERICHIA-COLI; ULTRAVIOLET; INACTIVATION; QUALITY; LIGHT; IRRADIATION; CYTOTOXICITY; PERFORMANCE; SAFETY; WATER; Science & Technology - Other Topics